Effects of Social Economy Selected Segments in The Slovak Republic - Chreneková Marcela (European Countryside, 2019)
The exclusion of individuals from the labour market directly affects the economic situation of their households. The main objective of the social economy is to address this situation. With the development of the social economy, efforts to assess its effects are intensified. The ambition of the paper is to express the extent of social economy in terms of rurality of regions of the Slovak Republic, identify its actors, sectors, where its entities operate and to illustrate both direct and indirect effects of the social economy. Industrial production is the most attractive sector for Slovak social enterprises. A small proportion of social enterprises operate in information, communication services and education. The largest number of sheltered workshops and workplaces operates in wholesale and retail trade and services related to sales. Geographical distribution of the social economy entities in Slovak districts (LAU 1) showed dependence of social economy intensity on rurality. Impact of a social enterprise is strongest in the local territory. However, single social enterprise can bring wide regional, national and even supranational effects.